2015
DOI: 10.1002/icd.1948
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Early Maternal Mental Health and Child Cortisol Regulation

Abstract: Maternal mental health problems can negatively impact children's physiological stress regulation. Yet, little is known of their long‐term effects, especially related to the timing of maternal symptoms. We examined how maternal mental health problems during pregnancy versus in the early postpartum period predict children's cortisol levels and diurnal patterns at 10–12 years. Participants were a selection (N = 102) of an original sample of 805 Finnish families, who were followed from the second trimester of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Furthermore, maternal prenatal and postnatal mental health problems may be differentially associated with later outcomes in the offspring. For instance, Vänskä et al (2015) showed that both maternal prenatal and postnatal mental health problems predicted children's later stress regulation, but in unique ways (maternal prenatal mental health problems predicted an intensified CAR, whereas mothers’ early postpartum mental health problems predicted a reduced CAR). Future research will hopefully explore in more detail the combination of early life stress, genetics, and ongoing stress that may ultimately determine an individual's responsiveness to stress and the vulnerability or resilience in developmental outcomes, such as EFs and psychiatric disorders (e.g., depression; Charney & Manji, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, maternal prenatal and postnatal mental health problems may be differentially associated with later outcomes in the offspring. For instance, Vänskä et al (2015) showed that both maternal prenatal and postnatal mental health problems predicted children's later stress regulation, but in unique ways (maternal prenatal mental health problems predicted an intensified CAR, whereas mothers’ early postpartum mental health problems predicted a reduced CAR). Future research will hopefully explore in more detail the combination of early life stress, genetics, and ongoing stress that may ultimately determine an individual's responsiveness to stress and the vulnerability or resilience in developmental outcomes, such as EFs and psychiatric disorders (e.g., depression; Charney & Manji, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these and some additional studies indicate that prenatal stress is linked to both raised diurnal cortisol levels and increased stress responsivity in infancy (Brennan et al, 2008; Davis, Glynn, Waffarn, & Sandman, 2011; Diego et al, 2004; Grant et al, 2009; Tollenaar, Beijers, Jansen, Riksen-Walraven, & de Weerth, 2011), and early to middle childhood (Gutteling, de Weerth, & Buitelaar, 2004, 2005; O'Connor et al, 2005; Simons, Beijers, Cillessen, & de Weerth, 2015). Later in development, some studies have found either a reduced cortisol awakening response (CAR) and blunted diurnal cortisol decline in adolescents (O'Donnell et al, 2013; van den Bergh et al, 2008, however, see Vänskä et al, 2015, for an intensified CAR but nonaffected diurnal cortisol decline in 10- to 12-year-olds) or no differences in diurnal patterns but increased cortisol reactivity during the Trier Social Stress Test among young adults exposed to early stress versus an age-matched comparison group (Entringer, Kumsta, Hellhammer, Wadhwa, & Wust, 2009).…”
Section: Prenatal Maternal Mood Shaping Child Stress Regulationmentioning
confidence: 99%
“…Associations with baseline HPA axis regulation are observed in childhood as well. In a prospective longitudinal investigation, prenatal maternal depressive symptoms were associated with a larger CAR in the offspring at 10 to 12 years of age, after covarying for postnatal factors including maternal depression (Vänskä et al, 2016).…”
Section: Processes and Risks By Which Prenatal Maternal Depression Mamentioning
confidence: 99%
“…studies have shown that symptoms of prenatal anxiety are related to higher cortisol levels during infancy (Beijers, Buitelaar, & de Weerth, 2014;De Bruijn et al, 2009;Glover, Ahmed-Salim, & Capron, 2016;Romero-Gonzalez, Caparros-Gonzalez, Gonzalez-Perez, Delgado-Puertas, & Peralta-Ramirez, 2018) and even in adolescence (Vänskä et al, 2016). As for perinatal variables, the data show that difficult deliveries (e.g., deliveries involving forceps, vacuum, or caesarean section) are related to higher infant cortisol levels.…”
Section: Discussionmentioning
confidence: 88%
“…Trait anxiety is a relatively stable personality feature, and subjects with high scores on this scale are emotionally unstable, submissive, frustrated, and show a tendency to perceive situations as threatening (Spielberger et al, ). Additionally, previous studies have shown that symptoms of prenatal anxiety are related to higher cortisol levels during infancy (Beijers, Buitelaar, & de Weerth, ; De Bruijn et al, ; Glover, Ahmed‐Salim, & Capron, ; Romero‐Gonzalez, Caparros‐Gonzalez, Gonzalez‐Perez, Delgado‐Puertas, & Peralta‐Ramirez, ) and even in adolescence (Vänskä et al, ). As for perinatal variables, the data show that difficult deliveries (e.g., deliveries involving forceps, vacuum, or caesarean section) are related to higher infant cortisol levels.…”
Section: Discussionmentioning
confidence: 96%